(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rosalia S, Yonariza, Syahrawati M. 2022. Effect of farmer’s behavior in cocoa management on insect diversity in Salayo Cocoa Plantation, West Sumatra, Indonesia. Biodiversitas 23: 5064-5073. The behavior of farmers in cocoa cultivation will affect the cocoa (Theobroma cacao) plantation environment and all living things in it, including insects. Disruption of insect diversity will also affect the ecosystem services insects provide, especially those related to improving the quality and quantity of agricultural products, especially cocoa. This study aimed to determine and analyze the diversity of insects in cocoa plantations and the role of insects in the ecosystem. This research was carried out at the Salayo Cocoa Plantation, a small-scale farmers’ cocoa plantation in Nagari Salayo, Kubung District, Solok Regency, and the Bioecology Laboratory, Plant Protection Department, Faculty of Agriculture, Andalas University, from July to October 2021. Insect collection was carried out using pitfall traps, yellow sticky traps, light traps, and spraying with insecticides. Insect sampling was carried out three times. The results showed that in cocoa plantations in Nagari Salayo, Kubung District, Solok Regency, insects from 12 orders, 31 families, and 58 species with a total number of 750 individuals were found, and insect diversity was in the range of 1-3322. Based on their role, the collected insects can be divided into pests, decomposers, pollinators, predators, parasitoids, and neutral insects. The richness and abundance of herbivores were lower than carnivores (predators and parasitoids). The predators with the highest number were Formicidae (Hymenoptera). Good farmer behavior in managing the cocoa plantation can maintain insect diversity and the sustainability of ecosystem services provided by insects.